Learning from instructional animations: How does prior knowledge mediate the effect of visual cues? - Arslan‐Ari, I. (Journal of computer assisted learning, 2018)
The purpose of this study was to investigate the effects of cueing and prior knowledge on learning and mental effort of students studying an animation with narration. This study employed a 2 (no cueing vs. visual cueing) × 2 (low vs. high prior knowledge) between‐subjects factorial design. The results revealed a significant interaction effect between prior knowledge and cueing on learning. Low prior knowledge learners had higher scores after studying an instructional animation with visual cues, compared to those who studied the same instructional animation without visual cues. Conversely, when cues were not provided, high prior knowledge learners outperformed those high prior knowledge learners who studied with the cued version of an instructional animation. These results indicated that the effects of cueing in an instructional animation change depending on the learners' level of prior knowledge. Specifically, low prior knowledge learners benefited more when visual cues were provided, whereas cues did not facilitate learning for high prior knowledge learners. Lay Description What is already known about this topic: Due to the transitory nature of information presentation in an animation, learners might not attend the relevant information before the information decays. Visual cues enhance the effectiveness of animations by directing the learners' attention to the relevant information at the right moment and by freeing up working memory resources for meaningful learning. Design principles that are effective for low prior knowledge learners might not be effective for high prior knowledge learners. Limited number of studies investigated the interaction between prior knowledge and cueing in multimedia learning. What this paper adds: The present study contributed to the literature on visual cueing in multimedia learning by examining the effects of cueing in an instructional animation and prior knowledge simultaneously. Prior knowledge mediated the effect of cueing on learning in an instructional animation about college level plant biology. Changing the colour of relevant text in an instructional animation enhanced learning for low prior knowledge learners but not for high prior knowledge learners. Implications for practice and/or policy: Educators and multimedia designers should consider learners' prior knowledge when designing instructional animations. Visual cues should be provided to low prior knowledge learners when they learn from a complex animation.